From land to the tiller to land liberalisation: the political economy of Gujarat's shifting land policy - Sud, N (Cambridge University Press, 2007)
Land is a metaphor for power, wealth and status. Independent Gujarat's initial mass-development strategy centered on agriculture but the emphasis was on productivity and efficiency rather than land redistribution or social justice. A state apparatus and socio-political set-up dominated by elite landed upper and middle castes and classes ensured this. Primary fieldwork-based research shows that by the mid-1980s, with a growing acceptance of ideas of liberalisation at the national and international level, the elite consensus on land began to shift. This shift must also be placed within local socio-economic developments that had propelled dominant landed groups into agro-industry and small scale industry in the last third of the twentieth century. Gujarat's elite still wanted to control land, but they did not want the state to regulate land use or continue emphasising the diluted but powerful rhetoric of land to the tiller. The rightward shift of all political formations in Gujarat after 1985 and the growing importance of the upper caste-middle class merchant-trader-builder-small businessman dominated Bharatiya Janata Party further facilitated the moves towards a shift in land policy. Continuing changes in Gujarat's land policy are determinedly moving towards the complete liberalisation of land.